Food safety, plastics and sustainability materials, chemicals, recycling and the circular economy - Fink, Johannes Karl (Hoboken, New Jersey John Wiley & Sons, Incorporated, 2023)
This book focuses on plastics for food safety, materials, chemicals and methods, as well as the applications of these polymers. The book begins with a chapter on food safety. Here, food security and the issues of migration of substances from packaging into the corresponding food, as well as the impact of microplastics on humans and the environment are discussed. In the next chapter, regulations, standards, and specifications are detailed. In another chapter, testing methods, such as risk assessment, freshness testing of food, and food colorants are discussed. In the chapter entitled "Food Packaging", the methods that can be used for these issues are given as well as the special materials for food packaging. The chapter on materials includes a discussion on nanocomposites, biopolymers, microplastics, and edible films. This is followed by chapters on additives and applications, such as functional food applications. The final chapter covers the identification of the materials, the methods for recycling, plastic waste generation, and post-consumer polyolefins. Three separate indexes ensure a reader/user-friendly experience
Includes bibliographical references.
Keywords: Food -- Safety measures